Issue of hiring a criminal - Ismail, Fadillah; Sim, Siaw Chien; Ali Hassan Humaid Alhosani, Adnan; Salleh, Siti Hasliah (Penerbit UTHM, 2020)
Hiring a criminal. Criminal refers to a person who has committed to the crime. In some other words, there is a crime that called as felony. Felony is a crime that classified as the most serious type of offenses such as fraud, physical harm or large scale of theft. Thus, hiring a criminal is defined as company wanted to hire a person who has criminal records background as an employee. Nowadays, criminal history is quite common in the country like USA, which has over 6.6 million people been under correctional supervision such as jail, prison and parole. According to Kurlychek, Bushway, & Denver (2019), employers were asked questions regarding to the criminal history and use various methods and sources to collect the criminal background information. In contrast, some companies would prefer to hire people who are nominated and found that prison record of felony convictions reduced the employer’s motivation to hire an employee (Griffith & Young, 2017). Thus, employers are making decision based on the criminal history and checks for the record to make the hiring decisions (Young & Ryan, 2019) even though the connection between the criminal records and the employment is still at the infancy stage (Griffith, Rade, & Anazodo, 2019). In recent years, the policy attention is focus on the employment for the people who has criminal background (Agan & Starr, 2017). Consequently, “Ban the Box” policies has created to revise when and how the criminal histories were disclosed to move forward to the fair chance of employment selection process (Griffith & Young, 2017) to prevent the inequalities of economics and racial problems (Agan & Starr, 2017).